Asupan zat gizi makro dan kenaikan berat badan selama hamil terhadap luaran kehamilan - Imelda Fitri; Rizki Natia Wiji (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2018)
Background: Based on neonatal nursing installation data at Arifin Achmad Regional Hospital in Riau Province, newborns with low birth weight have always been the highest cases.Objective: This study aimed to examine the effect of macronutrient status (carbohydrate, protein, fat) and gestational weight gain on pregnancy outcomes.Method: The design used in this study was case-control. The study sample was 74 respondents, the case group was 37 mothers with babies born with low birth weight and the control group was 37 mothers with babies born with normal birth weight. Macronutrient intake was collected with a food frequency questionnaire (FFQ). Data were analyzed by using the Chi-Square test (p<0,05).Results: Intake of low carbohydrate has 3 times risk for low birth weight (OR=3.46; 95%CI:1.25-9.47), intake of low fat has 5 times risk for low birth weight (OR=5.11; 95%CI:1.88-13.93), and intake of low protein has a 12 times risk for low birth weight (OR=12.21; 95%CI:3,97-37,94). A gestational weight gain is not following the IOM recommendations increased the risk of giving birth to a low weight baby (OR=3,96; 95%CI:1,49-10,53).Conclusion: Pregnant women with a low intake of carbohydrates, proteins, fats, and weight gain are not following the recommended increased the risk of giving birth to a low weight baby.